Viewing Personal Data Over Time - Knoll, Sonja; Hoff, Aaron; Fisher, Danyel; Dumais, Susan; Cutrell, Ed (2009)
Desktop search applications are changing the way we interact with personal information: we have a choice of whether to view files within their traditional siloed hierarchies, or brought together in search results. In this position paper, we discuss the advantages of temporal ordering of desktop search results, and present an interface that aggregates search results over time.
CHI 2009 Workshop on Interacting with Temporal Data